TIPOLOGI PERGERAKAN DAKWAH ISLAM DI INDONESIA - Dudung Abdul Rohman (Tatar Pasundan : Jurnal Diklat Keagamaan, 2018)
The dynamics of Islamic propagation movement in Indonesia continues to grow significantly. From since its presence until now, the movement of Islamic propagation in Indonesia beloved country continues to show proud results. Although there are obstacles with the occurrence of religious violence events. But in general, Islamic da'wah development in Indonesia is more robust and dynamic. A condition of attainment of da'wah that must be maintained and developed. When looking at the aspect of the form of movement, at least against the three typologies, namely: the movement of propagation in structural, cultural, and social mobility. These three movements have advantages and disadvantages, so complement and complement each other to advance the da'wah of Islam in Indonesia. How is the typology of Islamic propagation movement, here is the explanation.  Key words: Da'wah, Jihad, Hijrah, Culture, Social Mobility, Structural.